Can agricultural production stability reduce price volatility? - Seok, Jun Ho; Chung, Dae Hee; Moon, Hanpil (Korean Journal of Agricultural Science, 2024)
This study analyzes the effect of Korea’s domestic agricultural production and import on agricultural product price volatility from 1990 to 2022 using annual data. By applying the autoregressive distributed lag model that estimates both long- and short-term effects, we found that domestic agricultural production and import have a negative (-) relationship with agricultural price volatility in both the long and short-term. This implies that when there is a shock to the supply of domestic and overseas agricultural products, the volatility of agricultural products increases. In particular, the magnitude of the effect on the volatility of agricultural prices was found to be very large in the production of domestic agricultural products compared to imports. This result suggests that stabilizing the production of domestic agricultural products is important in stably managing agricultural prices, and shows where the effective policy direction is in terms of price stability.